Towards the design of an assurance framework for increasing security and privacy in connected vehicles. (23rd December 2020) - Kalloniatis, Christos; Diamantopoulou, Vasiliki; Kotis, Konstantinos; Lyvas, Christos; Maliatsos, Konstantinos; Gay, Matthieu; Kanatas, Αthanasios G.; Lambrinoudakis, Costas
Intelligent transport systems (ITS) play a key role in our daily activities. ITS development over the last decades has been based on the rapid evolution of information and communication technologies (ICT), which include processing capabilities, availability of hardware and communication technologies. However, as the development of ITS services increases so does the users' awareness regarding the degree of trust that they demonstrate on adopting this kind of services. This has brought to light several security and privacy concerns that ITS analysts should consider when designing and implementing various IT related services. This paper identifies how risk analysis can interact with security and privacy requirements' engineering world, in order to provide a holistic approach for reasoning about security and privacy in such complex environments like ITS systems.